2022
DOI: 10.1002/slct.202104294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Silicon Carbide Nanoparticles as an Additive to Minimize Surfactant Loss during Chemical Flooding

Abstract: Surfactant flooding is a prolific enhanced oil recovery technique. It alters the rock fluid interfacial interactions between reservoir fluids and rocks. However, a pair of impeding factors often limit the economic viability of the process and need to be optimized. The first is the surfactant loss on the adsorbent surface due to adsorption making it a potential environmental problem. The second is the Critical Micelle Concentration (CMC) which governs the amount of surfactant pumped. This study aimed to minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They concluded that Silicon Carbide Nanoparticles could minimize surfactant adsorption by 44 %. [44] Figure 8 displays a schematic illustration of the mechanism.…”
Section: Effect Of Msn Concentration With Surfactant Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that Silicon Carbide Nanoparticles could minimize surfactant adsorption by 44 %. [44] Figure 8 displays a schematic illustration of the mechanism.…”
Section: Effect Of Msn Concentration With Surfactant Solutionmentioning
confidence: 99%
“…Similar to our earlier experiments, the adsorption of surfactant particles at the sand surface was measured. [35,[44][45][46] In this work, 25 mL of 2500 ppm surfactant solutions with MSN of 100, 200, ChemistrySelect and 300 ppm concentration were prepared. A Labman Scientific Multiparameter LMMP-30 conductivity meter evaluated the samples for their conductivity.…”
Section: Surfactant Adsorptionmentioning
confidence: 99%
“…Based on the CT online experimental system, Yang et al explored the influence of pressure, permeability, and initial water saturation on imbibition distance according to changes in core water saturation during imbibition [44]. Ren et al investigated the imbibition recovery of carbonated water under high-pressure conditions through experimental design [45]. The research results showed that due to the unique properties of carbonated water, carbon dioxide diffusion also existed in the imbibition process to improve the imbibition recovery [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al investigated the imbibition recovery of carbonated water under high-pressure conditions through experimental design [45]. The research results showed that due to the unique properties of carbonated water, carbon dioxide diffusion also existed in the imbibition process to improve the imbibition recovery [45][46][47].…”
Section: Introductionmentioning
confidence: 99%